Pour un humanisme « europolite » (autour de The Renaissance Reform of the Book and Britain) - David Rundle (Diasporas: Circulations, Migrations, Histoire)
David Rundle is the author of a monograph on the role of an international group of scribes and of English elites in the success achieved by humanist script during the fifteenth and early sixteenth centuries. In this, he challenges the conventional assumptions of a history of humanism which sees it as spreading from an Italian centre to further-flung peripheries. He focuses instead on the importance of cosmopolitan collaboration and on the migratory habits of the elites who nurtured humanism. In this interview, he discusses the principles and the methods of his research, clarifying some of the concepts and elaborating on the potential significance of its conclusions to other areas of enquiry.